2021
DOI: 10.3390/nano12010135
|View full text |Cite
|
Sign up to set email alerts
|

Growth Mechanism of Periodic-Structured MoS2 by Transmission Electron Microscopy

Abstract: Molybdenum disulfide (MoS2) was grown on a laser-processed periodic-hole sapphire substrate through chemical vapor deposition. The main purpose was to investigate the mechanism of MoS2 growth in substrate with a periodic structure. By controlling the amount and position of the precursor, adjusting the growth temperature and time, and setting the flow rate of argon gas, MoS2 grew in the region of the periodic holes. A series of various growth layer analyses of MoS2 were then confirmed by Raman spectroscopy, pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Barbeiro et al (2019) used NBI to study gastrointestinal endoscopy and found that NBI can be used as an important auxiliary image for WLI, which can improve the detection of gastrointestinal lesions. Apart from CAD, many biosensors have been recently researched to detect different cancer types [ 35 , 36 , 37 ]. However, most of these biosensors have a high limit of detection, thereby leading to poor sensitivity in early-stage cancer detection.…”
Section: Introductionmentioning
confidence: 99%
“…Barbeiro et al (2019) used NBI to study gastrointestinal endoscopy and found that NBI can be used as an important auxiliary image for WLI, which can improve the detection of gastrointestinal lesions. Apart from CAD, many biosensors have been recently researched to detect different cancer types [ 35 , 36 , 37 ]. However, most of these biosensors have a high limit of detection, thereby leading to poor sensitivity in early-stage cancer detection.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, detecting esophageal cancer in its early stage is vital to increasing the five-year survival rate. One of the methods of detecting esophageal cancer is through a biosensor; however, most biosensors cannot detect cancer at the early stages [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…One way to detect cancer during its early stages is by using a cancer biosensor [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The specificity, quickness, compactness, and price of a biosensor present prospects for regionalized medical diagnoses [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted on various biosensors used to diagnose cancer lesions [ 27 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. A typical biosensor comprises a target cancer marker and a corresponding biotransducer, which is essential to the identification of the technical specifications of a device and a bioreceptor [ 39 ].…”
Section: Introductionmentioning
confidence: 99%